The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1590/1516-3180.2020.0046.r1.26062020
|View full text |Cite
|
Sign up to set email alerts
|

Structural validity of the Brazilian version of the Western Ontario and McMaster Universities Osteoarthritis Index among patients with knee osteoarthritis

Abstract: BACKGROUND: The original structure of the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) has been contested in several languages. OBJECTIVE: To assess the structural validity of the Brazilian version of WOMAC among patients with knee osteoarthritis. DESIGN AND SETTING: Structural validity study conducted at physiotherapy clinics and primary healthcare units. METHODS: The study included males… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 20 publications
2
9
0
Order By: Relevance
“…The Brazilian Portuguese version has three domains: pain (items 1, 2, 3, 4, and 5), stiffness (items 6 and 7), and physical function (items 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, and 24). However, Ferreira et al 17 found that the Brazilian version of the WOMAC with two domains (pain, 4 items; physical function, 8 items) presents a more adequate structure. For each item, there are options of five responses (0–4); the score for each domain is calculated as the simple sum of the answered items: pain domain (0–20), stiffness (0–8), and physical function (0–68); the higher the score, the greater the impact of osteoarthritis on the domains.…”
Section: Methodsmentioning
confidence: 99%
“…The Brazilian Portuguese version has three domains: pain (items 1, 2, 3, 4, and 5), stiffness (items 6 and 7), and physical function (items 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, and 24). However, Ferreira et al 17 found that the Brazilian version of the WOMAC with two domains (pain, 4 items; physical function, 8 items) presents a more adequate structure. For each item, there are options of five responses (0–4); the score for each domain is calculated as the simple sum of the answered items: pain domain (0–20), stiffness (0–8), and physical function (0–68); the higher the score, the greater the impact of osteoarthritis on the domains.…”
Section: Methodsmentioning
confidence: 99%
“…WOMAC can be completed in a short time, and its reliability and sensitivity have been proven in different languages, with a scale test-retest reliability of 0.83 and a validity of 0.77. (31)(32)(33) As it is a selfadministered measurement, the participants will complete the measurements themselves. The study personnel will not be allowed to assist the participant to answer any of the questions; however, they will be required to check that all the questions have been completed before the patients complete all the assessments.…”
Section: Primary Outcomes Womacmentioning
confidence: 99%
“…However, this study comes from a master's thesis and has not gone through a peer review process for publication in any scientific journal. Understanding this scenario, the rationale for testing the properties of the Brazilian Portuguese SV-WOMAC knee came from the results of Ferreira et al [12], who carried out the structural validity. And unlike the original version, with 24 items and 3 domains, it was reported that the best version of the WOMAC Knee with 2 domains and 12 items [12].…”
Section: Introductionmentioning
confidence: 99%
“…Understanding this scenario, the rationale for testing the properties of the Brazilian Portuguese SV-WOMAC knee came from the results of Ferreira et al [12], who carried out the structural validity. And unlike the original version, with 24 items and 3 domains, it was reported that the best version of the WOMAC Knee with 2 domains and 12 items [12]. After these results, it became necessary to carry out this study so that it would be possible to verify, through adequate and solid clinometric bases, whether this questionnaire provides reliable data on the pain and physical function of individuals with knee osteoarthritis.…”
Section: Introductionmentioning
confidence: 99%